Evaluation of a culturally sensitive social and emotional well‐being program for Aboriginal and Torres Strait Islanders. (9th August 2020) - Snodgrass, William J.; Rayner, Victoria; Rice, Simon M.; Purcell, Rosemary; Bowers, Jennifer
Abstract: Objective: To evaluate Deadly Thinking, a social and emotional well‐being promotion program targeted to remote and rural Aboriginal and Torres Strait Islander communities. Deadly Thinking aims to improve emotional health literacy, psychological well‐being and attitudes towards associated help‐seeking. Design: Participants completed pre/post‐test evaluations via a brief self‐report survey immediately before and after the Deadly Thinking workshop. Setting: Aboriginal and Torres Strait Islander communities in rural and regional Australia. Participants: Data were obtained from 413 participants (69.8% female, mean age 41.6 years), of whom 70.4% identified as Aboriginal or Torres Strait Islanders. Intervention: Deadly Thinking workshops involve participant's engaging with a series of videos and facilitated group discussions with other participants related to social and emotional well‐being topics relevant to individuals and communities. Main outcome measures: Participants completed measures of psychological distress, suicidal ideation, substance use, changes in attitudes towards help‐seeking and help‐seeking intentions and satisfaction with the workshop. Additionally, participants in a train‐the‐trainer workshop rated their perceived confidence to deliver the program post‐workshop. Result: Participants reported positive perceptions of community safety and well‐being and low rates of marked distress, with no significant difference between train‐the‐trainer and community workshop participants. Results indicated significant improvement in help‐seeking intentions post‐workshop and high rates of satisfaction with workshop components. Conclusion: Initial evaluation indicates good acceptability and feasibility of delivering the Deadly Thinking program in rural and remote Indigenous communities; however, more robust evaluation of the program is warranted using controlled conditions to measure effectiveness, particularly for changing in help‐seeking behaviour.